Mexico : Technical Assistance Report-Strengthening Public Assets and Liabilities Management. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2021)
The Ministry of Finance and Public Credit (SHCP) of Mexico intends to strengthen public asset and liability management (ALM) practices. The 2018 Fiscal Transparency Evaluation (FTE) identified several gaps in reporting public sector assets and liabilities and analysis of the associated risks. The authorities have identified the need for further reforms in three interrelated areas: (i) adopt the public sector balance sheet (PSBS) analytical framework to inform policy making; (ii) move toward more active cash management; and (iii) strengthen the management of financial assets and introduce a sovereign assets and liabilities management (SALM) framework in a phased manner. This report provides recommendations for reforms in these three areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Mexico